The value of intermediation in the stock market - Di Maggio, Marco; Egan, Mark; Franzoni, Francesco (Journal of Financial Economics, 2022)
We estimate a structural model of broker choice to quantitatively decompose the value that institutional investors attach to broker services. Studying over 300 million institutional equity trades, we find that investors are sensitive to both explicit and implicit trading costs and are willing to pay a premium for access to formal and informal research. Formal and informal research account for roughly half of the value generated by brokers. In addition, we use our model to investigate soft dollar arrangements, where research and execution services are bundled, and find that such arrangements allow hedge funds and mutual funds to underreport management fees by 10%.